Comparison of selected mental skills between elite and non-elite male and female taekwondo athletes - Sotoodeh, M. S.; Talebi, R.; Hemayattalab, R.; Arabameri, E. (World Journal of Sport Sciences, 2012)
The purpose of this study was to compare selected mental skills in elite and non-elite taekwondo athletes. 88 male and 54 female taekwondo athletes (elite=60, non-elite=82) answered Ottawa Mental Skills Assessment Tools (version 3). This questionnaire assessed three categories of mental skills: foundation skills, psycho-somatic skills and cognitive skills. The results of 2×2 MANOVA revealed a significant difference between male and female athletes only in activation factor. Also, elite athletes significantly used game planning, goal setting, activation, relaxation, self-confidence and commitment more than non-elite athletes. However, non-elite athletes were better than elite athletes in refocusing and stress reaction. According to the results of this study, it is recommended that taekwondo coaches improved game planning, goal setting, activation, selfconfidence and commitment factors in non-elite taekwondo athletes. Elite taekwondo athletes also should develop their refocusing and stress reaction to maintain their skill level.